The Effectiveness of Group Counselling with Modelling Technique to Improve Self-Efficacy in Senior High School Students Decision Making of Study Continuation - Bisri, Muhammad; Purwanto, Edy; Japar, Muhammad (Jurnal Bimbingan Konseling, 2018)
The purpose of this study was to test the effectiveness of group counseling using modeling techniques to improve self-efficacy decision making of study continuation in senior high school students. The research method of present study was experimental design, particular by Randomized Pretest-Postest Comparison Group design, and involving 18 students as participants who selected random assignment from students of class XII SMA Al-Azhar Menganti Gresik. The result of analysis using One way ANOVA showed that group counseling  using modeling techniques effective to improve self-efficacy decision making of  study continuation in students (F(2,24) = 69.016; p < 0.01). The results of this study indicate that students who received group counseling services with combined techniques experienced improved self-efficacy of advanced study decision making higher than students who received group counseling services with live modeling techniques.